2020
DOI: 10.1002/alz.039996
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cortical thickness in World Trade Center responders with cognitive impairment

Abstract: Background Recent reports suggest that World Trade Center (WTC) responders are at increased risk for cognitive impairment (CI). The current study utilized neuroimaging to determine whether WTC responders with CI have reduced cortical thickness (CTX). Method WTC responders (N=99) with and without CI, recruited from an epidemiologic study of cognitive aging among WTC responders, participated in a neuroimaging study that included a T1‐MPRAGE protocol. CTX was computed in 34 Desikan‐Killiany atlas regions of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 51 publications
8
40
0
Order By: Relevance
“…These results build on previous work in this population noting that cognitive impairment occurs at approximately twice the rate of population controls for people 10 to 20 years older. 32 These findings echo those from studies of veterans and certain other survivors of trauma that have shown PTSD and depressive symptoms are risk factors for mental dysfunction. [33][34][35] Though forgetfulness can sometimes simply be a result of age, this recent research reported that the cognitive effects were similar for both younger and older members of the study group.…”
Section: Discussionsupporting
confidence: 62%
“…These results build on previous work in this population noting that cognitive impairment occurs at approximately twice the rate of population controls for people 10 to 20 years older. 32 These findings echo those from studies of veterans and certain other survivors of trauma that have shown PTSD and depressive symptoms are risk factors for mental dysfunction. [33][34][35] Though forgetfulness can sometimes simply be a result of age, this recent research reported that the cognitive effects were similar for both younger and older members of the study group.…”
Section: Discussionsupporting
confidence: 62%
“…Calculation of the WTC FI-Clinical does not require collection of any additional data elements, thus paving the way for large-scale retrospective analyses of aging within this cohort. Also, this measure will be useful for current and future WTC research projects focused on the long-term health and well-being of responders across a number of areas, for example, cognitive health, which is already an ongoing area of focus (Clouston et al, 2019(Clouston et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have observed elevated risk of various cancers among this cohort (Shapiro et al, 2020;Solan et al, 2013). As the cohort ages, it is expected that responders, similar to older adults in the community, will accumulate multiple comorbidities and develop age-related syndromes such as osteoarthritis and hypertension (Fried et al, 2004); in fact, cognitive impacts are now also documented as WTCrelated "emerging conditions" (Clouston et al, 2020). Thus, there is a pressing need to characterize, assess, and monitor the development of age-related syndromes among this cohort, as the WTC exposures may alter the trajectory of aging among these responders.…”
Section: Introductionmentioning
confidence: 92%
“…As the at‐risk population ages, research into persistent and late‐emerging health effects are increasing in prominence. WTC Health Program research and surveillance programs have provided some preliminary evidence pointing to potential discovery of new associations between 9/11‐exposures and chronic health conditions, such as autoimmune diseases, 21–23 cardiovascular disease, 24–30 and neurological disorders 31–37 . Continued research involving these emerging conditions and others is an integral part of the WTC‐Health Program, including its important role in future changes to the list of qualifying health conditions 38…”
Section: Impacts From Existing Researchmentioning
confidence: 99%
“…As an example of emerging conditions research, there is some evidence suggesting increased mild cognitive impairment among responders, now at midlife, that might be attributable to 9/11 exposures 31–37 . Clouston et al (2016) was among the first to evaluate the association of PTSD and major depressive disorders with cognitive impairment in a sample of general responders 34 .…”
Section: Impacts From Existing Researchmentioning
confidence: 99%